Aurora at the pole and equator: overlapping functions of Aurora kinases in the mitotic spindle. Issue 3 (March 2013) - Hochegger, Helfrid; Hégarat, Nadia; Pereira-Leal, Jose B.
Abstract : The correct assembly and timely disassembly of the mitotic spindle is crucial for the propagation of the genome during cell division. Aurora kinases play a central role in orchestrating bipolar spindle establishment, chromosome alignment and segregation. In most eukaryotes, ranging from amoebas to humans, Aurora activity appears to be required both at the spindle pole and the kinetochore, and these activities are often split between two different Aurora paralogues, termed Aurora A and B. Polar and equatorial functions of Aurora kinases have generally been considered separately, with Aurora A being mostly involved in centrosome dynamics, whereas Aurora B coordinates kinetochore attachment and cytokinesis. However, double inactivation of both Aurora A and B results in a dramatic synergy that abolishes chromosome segregation. This suggests that these two activities jointly coordinate mitotic progression. Accordingly, recent evidence suggests that Aurora A and B work together in both spindle assembly in metaphase and disassembly in anaphase. Here, we provide an outlook on these shared functions of the Auroras, discuss the evolution of this family of mitotic kinases and speculate why Aurora kinase activity may be required at both ends of the spindle microtubules.